Association of Abdominal Incision Length With Gastrointestinal Function Recovery Post-operatively: A Multicenter Registry System-Based Retrospective Cohort Study - Song, Jianning; Yang, Yingchi; Guan, Wenxian; Jin, Gang; Yang, Yinmo; Chen, Lin; Wan, Yong; Li, Leping; He, Qingsi; Zhang, Wei; Zhu, Weiming; Chen, Lei; et al. (Frontiers in Surgery, 2021)
Objective: To evaluate the influence of the abdominal incision length on the gastrointestinal function recovery post-operatively. Background: Gut motility recovers more quickly after the minimally invasive laparoscopic surgery compared than after the traditional open surgery; however, whether the minimal abdominal incision contributes to the faster gut motility recovery is controversial and lacks solid clinical evidence. Methods: A registry-based secondary cohort analysis was conducted to evaluate the association between the abdominal incision length and gut motility recovery post-operatively based on a multicenter, prospective, and observational study of the prolonged post-operative ileus (PPOI) incidence and the risk factors in the patients with the major abdominal surgery. The incision length, in the centimeters, was the exposure. The primary outcome measures were the PPOI incidence and its association with the incision length. The secondary outcome included the days to the first passage of flatus and the days to the first passage of stool. Results: Overall, 1,840 patients, including 287 (15.7%) patients with the PPOI, were recruited. The PPOI incidence was 17.6% and 13.3% in the long-incision (>18 cm) and short-incision patients ( ≤ 18 cm), respectively. The incidence of the PPOI increased by 1.1% (1.0–1.1) by each centimeter increment of the incision length after adjusting for the confounding factors. In comparison to the short-incision patients, the long-incision patients had prolonged passage of stool (4.46 vs. 4.95 days, p < 0.001). Each centimeter increment of the incision length contributed to a 2% increased risk of delay in the first bowel movement [hazard ratio (HR) 0.980 (0.967, 0.994)]. Conclusion: A long abdominal incision length independently contributed to the prolonged gut function recovery post-operatively mainly by delaying the time to the first bowel movement, but not influencing the time to first passage of flatus.